Hepatocellular Adenoma in a Patient with Ornithine Transcarbamylase Deficiency. (2nd October 2019) - Cheng, Lin; Liu, Yajuan; Wang, Wenjing; Merritt, J. L.; Yeh, Matthew
Abstract : Ornithine transcarbamylase (OTC) deficiency is an X-linked recessive disorder that leads to hyperammonemia and liver damage. Hepatocellular adenoma in OTC deficiency patients has not been previously described. Here we report the first such case to be described in the English language scientific literature.